2018
DOI: 10.1097/dcc.0000000000000312
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Bed Bathing on Vital Signs and Oxygen Saturation in Children Who Are Connected to Mechanical Ventilation

Abstract: The bed bathing positively affected the vital signs and oxygen saturation values in intubated children connected to the mechanical ventilation. Yet, there is still a need for more research to test the effects of bed bathing on respiratory and circulatory function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…In studies conducted on premature infants and newborns, it was stated that the heart rate increased significantly during and immediately after bathing, whereas the heart rates began to decrease in subsequent measurements (Ar & Gözen, 2018; Çaka & Gözen, 2018; Lee, 2002; So et al, 2014; Tapia-Rombo et al, 2003; Taşdemir & Efe, 2019). In a study with children, Kızıl (2015) stated that the heart rate and systolic and diastolic blood pressure of children were found to be highest immediately after traditional bed baths and lowest 30 minutes afterwards.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In studies conducted on premature infants and newborns, it was stated that the heart rate increased significantly during and immediately after bathing, whereas the heart rates began to decrease in subsequent measurements (Ar & Gözen, 2018; Çaka & Gözen, 2018; Lee, 2002; So et al, 2014; Tapia-Rombo et al, 2003; Taşdemir & Efe, 2019). In a study with children, Kızıl (2015) stated that the heart rate and systolic and diastolic blood pressure of children were found to be highest immediately after traditional bed baths and lowest 30 minutes afterwards.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that bathing in adults and newborns caused heat loss, and measurements after bathing were found to be lower than those before bathing (Ar & Gözen, 2018; Çaka & Gözen, 2018; Ceylan & Bolışık, 2018; Edraki et al, 2014; Kuller, 2014; Taşdemir & Efe, 2019; Zaybak & Güneş, 2009). In a study in which the body temperatures of children who had traditional bed baths were analyzed, it was stated that the body temperature was the lowest immediately after the bath, and measurements taken 30 minutes after the bath were found below the values before bathing (Kızıl, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study on the effect of bed bathing on vital signs and oxygen saturation in children connected to mechanical ventilation on systolic blood pressure with p value = 0.000 (2).…”
Section: Discussionmentioning
confidence: 99%
“…Personal hygiene is an action to protect, maintain and improve skin hygiene and health (1,2). These actions are beneficial for physical well-being such as rest, sleep, eating and psychic well-being which can increase selfconfidence and increase patient comfort (3).…”
Section: Introductionmentioning
confidence: 99%